Satellite imagery from Neptune Pass, Louisiana, United States of America - Alexander Kolker; Dallon Weathers; Swann Christy; Renfro Alisha (PANGAEA, 2025)
This dataset contains satellite imagery of Neptune Pass, located on the east side of the lower Mississippi River in southeastern Louisiana, USA. The imagery was captured on 23 September 2022 and 14 October 2022. The purpose of this dataset is to support the analysis of the geomorphological evolution of Neptune Pass—the largest active distributary of the Mississippi River—and the delta it is forming in Quarantine Bay. The spatial extent of the study area ranges from 29.432838°N to 29.375311°N latitude and from -89.522739°W to -89.458791°W longitude. Satellite data were obtained from the Sentinel-2 mission, operated by the European Space Agency extquotesingles Copernicus program. Imagery was accessed through the Sentinel Hub platform (https://www.sentinel-hub.com) under the Copernicus open access data policy. The legal terms of use can be found at https://sentinel.esa.int/documents/247904/690755/Sentinel_Data_Legal_Notice.